Effect of Taurine on The Respiratory System of Rats - E.M, Ammer; A.A., Shaaban; H.A., Ghonem; H.A., Elkashef (Fakultas Farmasi, Universitas Gadjah Mada, 2013)
The present study was designed to investigate the effect of taurine on isolated trachea and pulmonary artery of rats and the possible mechanism(s) of action. The possible antioxidant effect of taurine was also studied by measuring its protective effect against cyclophosphamide induced lung injuiry. Taurine produced a concentration dependent relaxation in the isolated tracheal strips and pulmonary arterial rings precontracted by serotonin (2x10-4 mM). The relaxing effect of taurine was not influenced by pretreatment with nitric oxide synthase inhibitor (L-NAME) , cysteinyl leukotreines receptor 1 blocker (montelukast) , H1 receptor blocker (chlorpheniramine) , β-adrenoceptor blocker (propranolol), potassium channel blocker (amiodarone) , cyclo-oxygenase inhibitor (indomethacin) or muscarinic receptor blocker (atropine). Preincubation with adenosine receptor blocker (aminophylline) significantly potentiated the relaxing effect of taurine in the tracheal strips and pulmonary arterial rings. Cyclophosphamide (CYP, 150 mg/kg) administerated i.p. in a single dose was used to produce lung injuiry in rats. CYP caused marked increase in lung lipid peroxides (MDA) and decrease in lung reduced glutathione (GSH). Administration of taurine (1% in drinking water) starting 7 days before CYP and continuing throughout the duration of the experiment (24 hours) improved significantly the lung GSH and MDA. It can be concluded that taurine relaxes precontracted rat tracheal strips and pulmonary arterial rings probably by direct effect on the smooth muscles. Also, the observed antioxidant activity of taurine which may contribute to its relaxant effect suggesting the usefulness of turine in pulmonary hypertension.